(3TQM GdCQLhR aj GdbVGjG GdfLhejI dYdi Hf CHj GdQLGds - (3CMeO Hf GdMSf GdbfaPis; (3CMeO Hf GdMSf, GdbfaPj,J (B81 (3g` s ((3YHO GdefYe TQa s)
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3aEfi deG QCjJ CQLhRg GdaGVd CHj GdMSf Ydi Hf CHj GdQLGd GdcGJH GdbjQhGfi MGUQg dCcKQ GdbhGYO ai GdbVGjG GdfLhejI s
(3BNQgG (B:s
(3aEf bGQf GdfMS bhjJ OdGdJg hgGgfG GfJgi ZQV ai gPG GdeLehY GdeHGQc YdiTQW GdEjLGR hGdGNJUGQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B224 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B65 s
Keywords: (3Gdadcs